#### Answer

$$ y'= 27x(2+9x^2)^{1/2} .$$

#### Work Step by Step

Recall that $(x^n)'=nx^{n-1}$
Since $ y=(2+9x^2)^{3/2}$, then by the chain rule the derivative $ y'$ is given by
$$ y'=\frac{3}{2}(2+9x^2)^{1/2}(18x)=27x(2+9x^2)^{1/2} .$$

Published by
W. H. Freeman

ISBN 10:
1464125260

ISBN 13:
978-1-46412-526-3

$$ y'= 27x(2+9x^2)^{1/2} .$$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.